How Do Firms Adjust to Negative Labor Supply Shocks? Evidence from Migration Outflows - Emanuele Dicarlo (Institute of Labor Economics (IZA), 2022)
The quality of workers in a country positively relates to productivity of firms, adoption of new technologies, and growth. This paper studies adjustments of Italian firms to negative labor supply shocks in the context of workers' outflows from Italy to Switzerland. My diff-in-diff leverages the implementation of a policy in which Switzerland granted free labor market mobility to EU citizens and different treatment intensity of Italian firms based on their distance to the Swiss border. Using detailed social security data on the universe of Italian firms and workers, I document large (12 percentage points higher) outflows of workers and fewer (2.5 percentage points) surviving firms in the treatment group relative to control. Despite replacing workers and becoming more capital intensive, treated firms are less productive and pay lower wages. I investigate this evidence through the lens of a simple production function with high and low-skilled labor within a heterogeneity analysis based on the skill intensity of the industry of each firm. In line with the brain drain literature, I show how adverse effects of large outflows of workers operate through firms that workers leave. I provide suggestive evidence that high-skill intensive firms are the main driver of the negative results on wages and productivity. I also show that low skill intensive firms instead suffer less from losing workers and provide new job opportunities for the workers who do not migrate.
Keywords: F22; J22; J24; J61; 330; migration; labor supply; skills; firms